O ato de compreender na consulta mediúnica: um diálogo ensaístico entre guia, médium e consulente no terreiro de umbanda - Volponi, Rodrigo; Chiachiri, Roberto (Folios, revista de la Facultad de Comunicaciones y Filología, 2019)
This text has its theoretical and experiential grounds in inspirations gathered from studies on narrative and essay, on the complexity thinking and the notions of inter-, trans- and indisciplinarity. With higher strength the authors find support in the studies of comprehension as a method, to which the world of symbols and imaginary is as valuable and worthy as science as a human attempt to read and understand the world, in order to prepare this essay on Umbanda in Brazil. Speaking of method, the authors let themselves to go with the flow of the liberties permitted and provoked by the essay form, thus uniting theory and experience. Thus, the essay-text harmonizes with the life-text in the production of a possible dialogue, funded in mutual respect and admiration.